An 8kW LLC resonant converter in plasma power supply based on SiC power devices for efficiency improvement. Issue 4 (4th November 2019) - Wang, Zhenmin; Fan, Wenyan; Xie, Fangxiang; Ye, Chunxian
Abstract : Purpose: This paper aims to present an 8 kW LLC resonant converter designed for plasma power supply with higher efficiency and lighter structure. It presents how to solve the problems of large volume and weight, low performance and low efficiency of traditional plasma power supply. Design/methodology/approach: At present, conventional silicon (Si) power devices' switching performance is close to the theoretical limit determined by its material properties; the next-generation silicon carbide (SiC) power devices with outstanding advantages can be used to optimal design. This 8 kW LLC resonant converter prototype with silicon carbide (SiC) power devices with a modulated switching frequency ranges from 100  to 400 kHz. Findings: The experimental results show that the topology, switching loss, rectifier loss, transformer loss and drive circuit of the full-bridge LLC silicon carbide (SiC) plasma power supply can be optimized. Research limitations/implications: Due to the selected research object (plasma power supply), this study may have limited universality. The authors encourage the study of high frequency resonant converters for other applications such as argon arc welding. Practical implications: This study provides a practical application for users to improve the quality of plasma welding. Originality/value: The experimental results show that the full-bridge LLC silicon carbide (SiC) plasma power supply is preferred in operation under conditions of high frequency and high voltage. And its efficiency can reach 98%, making it lighter, more compact and more efficient than previous designs.